2009
DOI: 10.14411/eje.2009.081
|View full text |Cite
|
Sign up to set email alerts
|

The first holistic SEM study of Coniopterygidae (Neuroptera) - structural evidence and phylogenetic implications

Abstract: Abstract. Adults of two coniopterygid species, Aleuropteryx juniperi Ohm, 1968 (Aleuropteryginae) and Semidalis aleyrodiformis (Stephens, 1836) (Coniopteryginae), were studied using scanning electron microscopy. Interspecific differences in the ultrastructure of the integument of all the major parts of the body were identified and described, and the functional and phylogenetic implications of the differences discussed. Additionally, the enlarged terminal segment of the labial palps of the Coniopterygidae and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 23 publications
1
26
0
Order By: Relevance
“…In particular, morphological studies suggested that Mantispidae would be placed in a clade together with Berothidae, Rhachiberothidae and Dilaridae (the dilarid clade). Moreover, a sister-group relationship of Coniopterygidae + dilarid clade has been hypothesized (Aspöck et al 2001;Aspöck & Aspöck 2008;Zimmermann et al 2009;Beutel et al 2010). On the contrary, Hemerobiidae and Chrysopidae would have to be placed in a separate clade.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, morphological studies suggested that Mantispidae would be placed in a clade together with Berothidae, Rhachiberothidae and Dilaridae (the dilarid clade). Moreover, a sister-group relationship of Coniopterygidae + dilarid clade has been hypothesized (Aspöck et al 2001;Aspöck & Aspöck 2008;Zimmermann et al 2009;Beutel et al 2010). On the contrary, Hemerobiidae and Chrysopidae would have to be placed in a separate clade.…”
Section: Discussionmentioning
confidence: 99%
“…Achtelig 1967;Maki 1936;Röber 1942). Its presence in Plega (Ferris 1940) and Coniopterygidae (Zimmermann et al 2009: Semidalis and Aleuropteryx) certainly is an apomorphic condition.…”
Section: Phylogenetically Relevant Characters and Character Statesmentioning
confidence: 99%
“…They are also present in Brucheiserinae. But Zimmermann, Klepal, and Aspöck (2009) hypothesized the following relationships between the three subfamilies: (Brucheiserinae + Coniopteryginae) + Aleuropteryginae, on the basis of potential synapomorphies in the larvae. They concluded that the presence of abdominal plicatures could rather be a plesiomorphy.…”
Section: Discussionmentioning
confidence: 99%